Evaluation of the carotid arteries using grayscale and color Doppler ultrasonography in stroke patients - Acharya, Sandeep; Poudel, Saurav; Parajuli, Bivusha; Kaphle, Pratibha (Birat Journal of Health Sciences, 2025)
Introduction: Stroke causes neurological dysfunction by cerebral or spinal infarction. Ultrasound of the carotid arteries is beneficial for the management of carotid atherosclerosis. Multiple risk factors exist for the occurrence of large artery stroke. Methodology: This prospective descriptive study was conducted in a tertiary Care Centre from March 2023 to March 2024. Ethical clearance was taken from the Institutional Review Committee (Ref no: 816/2023). Purposive sampling was used to include 204 patients with stroke/transient ischemic attacks. Variables collected were demographics, evaluation of comorbidities, previous medical history, family history, and carotid ultrasound including grayscale and color Doppler. Results: The mean age of the patients was 68.39 ± 9.35 years with a male predominance. Carotid plaques were seen in 91.67%. The most common artery was the left common carotid and the most common type of plaque was the heterogeneous type. Severe narrowing of the arteries was seen in 20.09% with complete occlusion in 8.33% and 8.82% of cases in the right and left internal carotid arteries respectively. Increasing age, hypertension, diabetes, dyslipidemia, smoking, and family history were important risk factors for the occurrence of stroke. A carotid intima-medial thickness of over 1 mm was observed in 40.68% and 35.76% of the right and left common carotid arteries, respectively. Conclusion: Carotid gray scale ultrasonography revealed significant carotid plaque status in patients of stroke. The presence of comorbidities increases the risk of stroke and carotid plaque. Color Doppler ultrasound of carotids is a useful tool for managing carotid atherosclerosis.